2018
DOI: 10.11604/pamj.2018.29.170.14296
|View full text |Cite
|
Sign up to set email alerts
|

Profil et antibiosensibilité des bactéries pathogènes associées aux diarrhées chez les patients consultant à l’Hôpital Régional Annexe de Kousseri, Extrême-Nord Cameroun

Abstract: IntroductionDu fait de l'accès limité au laboratoire au Cameroun, la prise en charge des cas de diarrhée dans la plus part des formations sanitaires est basée sur le diagnostic de présomption. L'objectif de notre étude était de déterminer la distribution et la sensibilité aux antibiotiques habituellement prescrits contre les bactéries pathogènes associés aux diarrhées à l'Hôpital Régional Annexe de Kousseri(HRAK) de Juillet à Octobre 2015.MéthodesIl s'agissait d'une étude descriptive et transversale ciblant to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
4
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 9 publications
0
4
0
Order By: Relevance
“…Diarrhea remains the leading source of morbidity and mortality in children under 5 years of age worldwide with approximately 760,000 annual deaths [1] [2]. According to the World Health Organization, diarrheal infections are the second leading cause of death in children under 5 years of age after the Human Immunodeficiency Virus [3].…”
Section: Introductionmentioning
confidence: 99%
“…Diarrhea remains the leading source of morbidity and mortality in children under 5 years of age worldwide with approximately 760,000 annual deaths [1] [2]. According to the World Health Organization, diarrheal infections are the second leading cause of death in children under 5 years of age after the Human Immunodeficiency Virus [3].…”
Section: Introductionmentioning
confidence: 99%
“…This finding was lower compared with other studies in resource-limited countries like Nepal and Togo where the positivity rate was 52.2%, 47% respectively. [14][15][16] Specimen received n=2888…”
Section: Discussionmentioning
confidence: 99%
“…In a study conducted by Njunda et al [6], 4.5% of the cases of Shigella infection were recorded among children under 15 years old after stool examination in the Buea Health District, Buea, and the Southwest Region of Cameroon. It has also been reported that infantile diarrhoea is among the main causes of death in children under 5 years old in Cameroon, together with malaria, measles, and respiratory tract disease [7]. Humans are the main reservoir of Shigella bacteria since there is well-established human-to-human transmission by a fecal-oral route or the ingestion of contaminated food and/or water [8].…”
Section: Introductionmentioning
confidence: 99%
“…As a matter of fact, the chemistry of Diospyros gilletii and other Diospyros species has been studied and reported by several authors [14][15][16][17][18]. The research by Tameye [17], which detailed the extraction and isolation of pure compounds in various parts (leaves, stem bark, and twigs) of Diospyros gilletii, led to the identification of seven coumarins: 11-O-(E)-cinnamoylnorbergenin (1) (leaves), 4-O-p-hydroxybenzoylnorbergenin (2), 4-Ogalloylnorbergenin (3), norbergenin (4) (leaves, stem bark, and twigs), a per-acetylated derivative of 4-O-p-hydroxybenzoylnorbergenin (5), a per-allylated derivative of 4-O-phydroxybenzoylnorbergenin (6) (stem bark), and 11-O-p-hydroxybenzoylnorbergenin (7) (twigs) (Figure S1, Supplementary Materials); three pentacyclic triterpene acids: ursolic acid (8), ursolic acid 28-allyle (9) (leaves), and corosolic acid (10) (leaves and twigs); and five pentacyclic triterpenoids: lupeol (11) (leaves, stem bark, and twigs), betulin (12) (leaves and twigs), betulinic acid (13) (leaves and stem bark), oleanolic acid (14) (leaves), and rotundic acid (15) (twigs) (Figure S2, Supplementary Materials). Compounds 8, 10, 11, 13, and 14 were also identified in Diospyros fragrans by the same research group [18].…”
Section: Introductionmentioning
confidence: 99%